Aplikasi Pemuasaan dan Pemberian Pakan Berprobiotik pada Budidaya Ikan Patin di UPR Fish Under Crew, Indralaya Utara, Ogan Ilir - Sefti heza Dwinanti; Lingga Rian Saputra; Dade Jubaedah (Jurnal Pengabdian Pada Masyarakat, 2022)
Fish Under Crew, a group of fish farmers located at Pulau Semambu, Indralaya Utara, Ogan Ilir. It rears several fish commodities including catfish. The knowledge of fish farmers about best aquaculture practices are still low and cost production become main problem for them. Therefore, community service held on Aquaculture Department, Sriwijaya University conducted an alternative solution to solved its problem by providing information and pilot culture about fasting and refeeding with probiotic in catfish. The community service was carried out in July-August 2021. The fasting interval was one day then refeeding with commercial pellet enriched by probiotic. Day of culture was 30 days and it compared with batch control which was daily fed without probiotic. Prior and after community service, the fish farmers were interviewed about their knowledge. During fish rearing, the fish farmers also learnt about fish rearing parameters such as growth, survival rate, feed conversion ratio (FCR) and water quality. In the end of culture, fish farmers stated that they were willing to apply the technology.